The Buccaneer Farmer : Published in England under the Title "Askew's Victory" - Bindloss, Harold, 1866-1945 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Buccaneer Farmer" by Harold Bindloss is a novel written in the late 19th century. The story centers on Osborn, a country gentleman struggling to manage his estate and the challenges posed by greedy tenants and the burden of a complicated financial situation. The book explores themes of pride, familial duty, and the intricacies of rural life, as he navigates the expectations of both his family and his tenants. The opening of "The Buccaneer Farmer" introduces Osborn in his library, frustrated by mounting bills and the affairs of his estate that intrude on his leisure time. This chapter sets the stage for his character, revealing his overbearing nature and the tension within his family regarding their financial situation. His interactions with his son Gerald, who is caught between familial expectations and personal ambition, highlight the generational conflicts at play. As Osborn engages with his tenants, particularly regarding their struggles against a monopolistic coal merchant, the dynamics of power, economic hardship, and social duty begin to unfold, hinting at the larger conflicts that will arise throughout the novel. (This is an automatically generated summary.)
Release date is 2004-02-01
Produced by Juliet Sutherland, Beginners Projects, Mary Meehan, and the Online Distributed Proofreading Team
Keywords: Farmers -- Fiction